2018
DOI: 10.1242/bio.035592
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the sacrum requires down-regulation of sonic hedgehog signaling in the sacral intervertebral discs

Abstract: In humans, the sacrum forms an important component of the pelvic arch, and it transfers the weight of the body to the lower limbs. The sacrum is formed by collapse of the intervertebral discs (IVDs) between the five sacral vertebrae during childhood, and their fusion to form a single bone. We show that collapse of the sacral discs in the mouse is associated with the down-regulation of sonic hedgehog (SHH) signaling in the nucleus pulposus (NP) of the disc, and many aspects of this phenotype can be reversed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…These observations suggest that the unidentified pericellular structure described by Trout et al () around the nested CLCs is generated by the fusion of cell membranes of several NP cells as they form a syncytia. Next, we analysed whether the differentiated NP cells continued to express SHH, which is crucial for proliferation and maintenance of the reticular structure of NP cells in the neonatal mouse lumbar disc (Dahia, Mahoney, & Wylie, ) and sacral disc (Bonavita, Vincent, Pinelli, & Dahia, ). Shh expression is known to decline from postnatal day four to one year of age in mouse NP cells (Dahia, Mahoney, Durrani, & Wylie, ; Winkler et al, ).…”
Section: Introduction/results/discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggest that the unidentified pericellular structure described by Trout et al () around the nested CLCs is generated by the fusion of cell membranes of several NP cells as they form a syncytia. Next, we analysed whether the differentiated NP cells continued to express SHH, which is crucial for proliferation and maintenance of the reticular structure of NP cells in the neonatal mouse lumbar disc (Dahia, Mahoney, & Wylie, ) and sacral disc (Bonavita, Vincent, Pinelli, & Dahia, ). Shh expression is known to decline from postnatal day four to one year of age in mouse NP cells (Dahia, Mahoney, Durrani, & Wylie, ; Winkler et al, ).…”
Section: Introduction/results/discussionmentioning
confidence: 99%
“…In 18M old Shh LacZ mouse disc, 14.9% of CLC‐NP cells were β‐gal+ (Figure o and q). Results from previous studies show that SHH regulates expression of Brachyury ( Bra/T ) (Bonavita et al, ; Dahia et al, ), a key developmental molecule; hence, we analysed the expression of Bra , in CLC‐NP using its reporter allele where nuclear GFP is expressed under Bra promoter but inserted after the coding sequence of Bra gene ( T ‐nGFP , [Imuta, Kiyonari, Jang, Behringer, & Sasaki, ]). 28.8% of CLC‐NP cells were TnGFP+ in 16M old mouse lumbar discs (Figure p–q).…”
Section: Introduction/results/discussionmentioning
confidence: 99%
“…The presence of progenitor cells was also reported in human disc samples (Risbud et al, ). In a study of skeletally mature 12‐week‐old mice, it was found that only a subset of nucleus pulposus cells expressed the notochord marker CK19 in the sacral disc (Bonavita et al, ), supplying further evidence of increasing molecular heterogeneity in nucleus pulposus cells with aging. It is not yet known if this age‐related increase in molecular heterogeneity among sacral disc nucleus pulposus cells is a feature of other regions of the spine.…”
Section: Potential Therapies For Disc Regeneration and Treatment Of Bmentioning
confidence: 99%
“…In this same time frame, the responses to key developmental signaling pathways including SHH, WNT, BMP, TGFb, and PTHrP in all components of the disc are also reduced (Dahia et al, ). Expression of BRA, a downstream target of SHH, in the mouse lumbar and sacral disc is also reduced with age (Bonavita et al, ; Dahia et al, ; Winkler et al, ). Interestingly, expression of BRA is not uniform among nucleus pulposus cells, which suggests cellular heterogeneity among the nucleus pulposus cells during postnatal growth and aging (Dahia et al, ).…”
Section: Molecular and Pathological Changes In The Disc With Aging Anmentioning
confidence: 99%
See 1 more Smart Citation